2007
DOI: 10.1016/j.juro.2007.05.142
|View full text |Cite
|
Sign up to set email alerts
|

Oncological and Functional Outcome of Radical Cystectomy in Patients With Bladder Cancer and Obstructive Uropathy

Abstract: Patients with bladder cancer who have obstructive uremia usually present with locally advanced disease. Radical cystectomy is not associated with additional morbidity, provided that patients are adequately prepared before surgery by optimizing renal function. An adequate number of these patients achieve long-term disease-free survival after radical cystectomy. As the urinary diversion of choice, an ileal conduit appears to be safe in patients with serum creatinine less than 2.5 mg% at surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We recognize that the present study is limited by its retrospective design as well as by the fact that the preoperative imaging studies were not centrally reviewed by a single radiologist in the assessment of clinical stage, and that we do not have the data regarding the time interval from imaging to surgery to evaluate as a predictor of upstaging. Similarly, while we did find, as has been noted elsewhere [25,26], that preoperative renal obstruction was predictive of pathological extravesical disease, other clinical variables that may provide prognostic information for patients with cT2 tumours, such as noninvasive tumour stage at presentation [7] and the presence of lymphovascular invasion in the transurethral resection specimen [27], were not available in the present series for analysis. In addition, adjuvant chemotherapy regimens were not uniform, which may have limited our ability to discern the impact of postoperative treatment on survival.…”
Section: Discussionmentioning
confidence: 52%
“…We recognize that the present study is limited by its retrospective design as well as by the fact that the preoperative imaging studies were not centrally reviewed by a single radiologist in the assessment of clinical stage, and that we do not have the data regarding the time interval from imaging to surgery to evaluate as a predictor of upstaging. Similarly, while we did find, as has been noted elsewhere [25,26], that preoperative renal obstruction was predictive of pathological extravesical disease, other clinical variables that may provide prognostic information for patients with cT2 tumours, such as noninvasive tumour stage at presentation [7] and the presence of lymphovascular invasion in the transurethral resection specimen [27], were not available in the present series for analysis. In addition, adjuvant chemotherapy regimens were not uniform, which may have limited our ability to discern the impact of postoperative treatment on survival.…”
Section: Discussionmentioning
confidence: 52%
“…Gupta N et al . found that ileal conduit may not be ideal for patients with serum creatinine greater than 2.5 mg/dl 38 . To avoid severe renal toxicities caused by chemotherapeutic agents with nephrotoxic properties, drug dosages are usually reduced in patients with renal insufficiency, which may lead to sub-optimal drug concentrations and compromise treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[14] The perioperative mortality is higher compared to that reported by most of the contemporary series. [13] Systemic consequences of septic complications were the most common cause of perioperative death in our patients. Most of the septic complications are consequent to postoperative chest infection.…”
Section: Discussionmentioning
confidence: 99%
“…Ileal conduit, as the urinary diversion appears to be safe in patients with a serum creatinine of <2.5 mg% at surgery. [13]…”
Section: Discussionmentioning
confidence: 99%